Results of medical treatment with psyllium, lactobacillus, and tryptophan (Plurilac® Trio) in obstructive defecation syndrome - Valiyeva, Sayali; Tiso, Domenico; Cerri, Paolo; Pisciaroli, Antonio; Pietroletti, Renato (Frontiers in Surgery, 2024)
Introduction The term “obstructive defecation syndrome” (ODS) describes a complex condition characterized by defecatory disorders. Such a condition represents a significant proportion of patients, which is estimated to be up to 30% of patients affected by chronic constipation. Presently, a broad agreement has been reached on diagnostic studies, whereas the choice of treatment that aims to improve the quality of life and/or correct the prevalent abnormalities or all anatomical abnormalities remains controversial. Methods This was a retrospective cohort study on 174 patients out of a total of 232 with ODS who were observed in a specialized university unit of surgical coloproctology between 2018 and 2022. Clinical assessment included examining the values of the Agachan–Wexner constipation score and Patient Assessment of Constipation (PAC)-quality of life (QoL) scores, a full digital anorectal examination, anoscopy, RX defecography, and a urogynecological consultation; a functional anorectal test, an endoanal ultrasound, and colonoscopy were performed in select patients. The patients were reevaluated after an 8–10-week course of medical treatment based on a high-fiber diet and fluid intake and 6 g of psyllium combined with lactobacillus and tryptophan b.i.d. The results were analyzed by means of the Wilcoxon rank-sum test, comparing pretreatment scores with the results at the first follow-up visit. Results After 8–10 weeks of conservative treatment, 128 patients declared full satisfaction, 29 reported moderate satisfaction, and 17 (9.7%) declared no improvement. Among these 17, there were 5 patients with paradoxical puborectal contractions. The value of the Agachan–Wexner constipation score after treatment decreased from the pretreatment Agachan–Wexner constipation score mean value of 23.4 ± 3.7 (mean ± SD range 15–27) to a mean value of 5.3 ± 0.7 (range 3–8, p < 0.001). The quality of life improved, as shown by the PAC-QoL score, indicating great improvement in social relationships. Conclusions Given the benefits of conservative therapies, they represent a cornerstone in the treatment of ODS, a complex disorder. Diet and bulking agents are mandatory forms of treatment prior to making any surgical attempt, also considering the fact that the psychosomatic component of ODS is an essential prerequisite to match patient expectations.